Lignocellulosic Biomass Decomposition and Bioconversion - Zhina Lian; Xin Zhou (Fermentation)
Lignocellulosic biomass (LCB) offers numerous advantages as a sustainable energy resource, such as its abundance, degradability, environmental compatibility, non-toxic nature, and cost-effectiveness [...]